IMPLEMENTATION OF THE ROLE OF THE MILITARY POLICE IN OVERCOMING NARCOTICS CRIMES COMMITTED BY THE INDONESIAN NATIONAL ARMY (STUDY AT POMDAM I/BB) - Irfan Rizky Pradya; Ismaidar; Firman Halawa (PT. Radja Intercontinental Publishing, 2024)
Narcotics crimes are part of extraordinary crimes which result in dependence on the user so that the recovery process takes a very long time and requires a very long period of time to eliminate the effects of dependence on illegal drugs, drug dependence will affect a person's way of thinking, It's not just the mindset that has changed, but it has a big impact on state order or state security, for example narcotics perpetrators from among members of the TNI, who really threaten the state and can destroy the image of law enforcement institutions. The aim of this research is how the role of the Military Police plays in overcoming narcotics crimes committed by the Indonesian National Army (study at Pomdam I/BB) and what are the obstacle factors in overcoming narcotics crimes committed by the Indonesian National Army (study at Pomdam I/BB ). The results of this research in terms of the role of military police are the same as ordinary investigators and all procedures for perpetrators are the same, but there is a specialization in the position structure where the position is removed from the TNI institution, the obstacles experienced by the TNI in dealing with Narcotics Crime, in terms of Investigations, administrative sanctions, witnesses, inaccurate evidence and difficulty in obtaining information from suspects of narcotics crimes.